Impact of psychiatry and mental health journals published in Spanish. - Vega-Dienstmaier, Johann M. (2022)
Objective: To describe the impact of psychiatry and mental health journals published in Spanish. Material and Methods: The psychiatry and mental health journals published in Spanish and included in Scielo, Scopus and Google Scholar were identified. The following impact indicators were obtained for each journal: improved CiteScore (Scopus); h5 index and h5 median (Google Scholar); and impact factor based on 3 years and immediacy index (Scielo). Results: The journals with the greatest impact were from Spain (eg, Psicothema and Revista de Psiquiatría y Salud Mental), Colombia (eg, Revista Latinoamericana de Psicología and Revista Colombiana de Psiquiatría), Chile (eg, Terapia Psicológica and Psicoperspectivas), and Mexico (eg, Salud Mental and Revista Mexicana de Psicología). In Peru the most relevant journals were Revista de Psicología and Revista de Neuro-Psiquiatría. Conclusions: Among the international journals of psychiatry and mental health that accept articles in Spanish, the highest impact indicators were found in publications from Spain, with Psicothema outstanding.